2014
DOI: 10.3390/v6010201
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Hantavirus Risk in Southern Argentina: A GIS-Based Approach Combining Human Cases and Host Distribution

Abstract: We use a Species Distribution Modeling (SDM) approach along with Geographic Information Systems (GIS) techniques to examine the potential distribution of hantavirus pulmonary syndrome (HPS) caused by Andes virus (ANDV) in southern Argentina and, more precisely, define and estimate the area with the highest infection probability for humans, through the combination with the distribution map for the competent rodent host (Oligoryzomys longicaudatus). Sites with confirmed cases of HPS in the period 1995–2009 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 73 publications
2
15
1
1
Order By: Relevance
“…Despite having high sensitivity and identifying a large number of new cases (82%), this map predicted a higher incidence of cases than actually occurred throughout the state. Generally, the emergence of human diseases is often found to be more spatially restricted than the distribution of the reservoir host (Schmaljohn & Hjelle 1997, Andreo et al 2014, which seems to be the case for Hantavirus Pulmonary Syndrome in São Paulo. Therefore, it seems that our RRA map is strongly overestimating high risk, which may be due to the extrapolation of this risk map to the entire São Paulo State, using the original abundance data that was collected in Atlantic Forest areas.…”
Section: Discussionmentioning
confidence: 99%
“…Despite having high sensitivity and identifying a large number of new cases (82%), this map predicted a higher incidence of cases than actually occurred throughout the state. Generally, the emergence of human diseases is often found to be more spatially restricted than the distribution of the reservoir host (Schmaljohn & Hjelle 1997, Andreo et al 2014, which seems to be the case for Hantavirus Pulmonary Syndrome in São Paulo. Therefore, it seems that our RRA map is strongly overestimating high risk, which may be due to the extrapolation of this risk map to the entire São Paulo State, using the original abundance data that was collected in Atlantic Forest areas.…”
Section: Discussionmentioning
confidence: 99%
“…Andreo et al . () used species distribution modeling techniques to examine the potential distribution of HPS caused by Andes virus in southern Argentina. The authors found a high and positive correspondence among HPS occurrence and environmental features such as high annual mean precipitation, dry summers, low percentages of bare soil and low temperatures in the coldest month.…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, the probability of transmission of this virus among rodents is expected to be low from local emergence sites, at least in the area comprised by this study. Andreo et al (2014) used species distribution modeling techniques to examine the potential distribution of HPS caused by Andes virus in southern Argentina. The authors found a high and positive correspondence among HPS occurrence and environmental features such as high annual mean precipitation, dry summers, low percentages of bare soil and low temperatures in the coldest month.…”
Section: Landscape Scalementioning
confidence: 99%
“…The relation of landscape, climate and social factors associated with hantavirus transmission has been widely studied. The factor “precipitation” is the most studied climatic predictor of HCPS outbreaks, with several authors indicating a positive correlation with rodent densities and prevalence of hantavirus [33] , [34] , [35] , [36] , [37] , [38] . High rainfall increases vegetation growth, raising rodent densities and increasing the probability of human-rodent encounters and consequent hantavirus transmission [39] , [40] .…”
Section: Environmental Determinantsmentioning
confidence: 99%